A Clinical Approach of Allergic Rhinitis in Children - Ioannis Goniotakis; Evanthia Perikleous; Sotirios Fouzas; Paschalis Steiropoulos; Emmanouil Paraskakis (MDPI AG, 2023)
Allergic rhinitis is an important disease with a global footprint and a growing prevalence, affecting children and adults. Although it is commonly under-diagnosed and under-treated, it causes important social and economic effects (diminished quality of life, poor academic performance, escalated medical visits, heightened medication usage, and effects in other chronic conditions, e.g., asthma). It is characterized by distinctive, easily identifiable symptoms (sneezing, nasal discharge, nasal congestion, nasal-eye-palatal itching) and indirect accompanying indicators (fatigue and decreased school performance). The classification of allergic rhinitis hinges upon its nature and chronic distribution (seasonal or perennial) and its intensity, which spans from mild to moderate and severe. The diagnostic process primarily relies upon recognizing key clinical indicators, evaluating historical records, and considering risk factors. It is supported by abnormal laboratory findings, like in vitro allergen-specific IgE tests (enzyme immunoassay-EIA, chemiluminense immunoassay-CLIA) or in vivo skin prick tests for specific allergens. In the differential diagnosis, other chronic diseases manifesting with chronic rhinitis should be excluded (e.g., rhinosinusitis, chronic non-allergic rhinitis, rhinitis triggered by medications). The treatment of allergic rhinitis in children is mainly chronic and is focused on allergen exposure prevention, drug therapy, and immunotherapy in severe cases. Locally administered intranasal corticosteroids are the cornerstone of therapy. They are safe, effective, and have a favorable safety profile even during long-term use. Choosing a suitable intranasal corticosteroid drug with low systemic bioavailability makes long-term treatment even safer. Combinations of intranasal corticosteroids and H1 antihistamines are available in several countries and are widely used in more severe cases and the presence of year-round symptoms. Adding newer-generation oral H1-antihistamines broadens the available therapeutic inventory without significant effects compared to using previous-generation, once widely available, H1-antihistamines. Treatment of allergic rhinitis is complex and multi-dimensional, requiring an effective approach by a specialized group of specialized pediatricians, and is severely affected by the concurrent presence or development of other diseases in the spectrum of allergic diseases (conjunctivitis, asthma).